The political and legal specifics of the process of admitting the Republic of Macedonia (FYROM) to the UN (1991–1993) - Woźnica, Rafał; Krata, Cezary (Balcanica Posnaniensia. Acta et studia, 2025)
After declaring independence in 1991, the Republic of Macedonia faced the need to confirm its statehood on the international stage. However, despite meeting all the criteria for statehood, Greek actions meant that Macedonia faced unprecedented pressure and obstacles, and the process of international recognition dragged on for years. According to the Greek perspective, the name, flag, and the constitution of Macedonia represented a potential threat to the territorial integrity of Greece. Consequently, Greece denied the new state the right to its national symbols, and employed all available means to prevent the international recognition of Macedonia and its membership in international organizations. This article employs an analitycal approach to examine the process of the Republic of Macedonia's admission to the UN. In the initial section of the text, the authors present Macedonia's efforts to achieve international recognition within the European Community. The initial measures undertaken in this forum were a consequence of a consensus within the international system that the Macedonian issue should be resolved by European countries. However, despite the fact that the Republic of Macedonia met all the criteria for international recognition, it was delayed for political reasons. The authors then proceed to analyze the process of admitting the Republic of Macedonia to the UN. The procedure, characterized by the dispute with Greece, exhibited numerous deviations from standard procedures and accepted norms. The authors contend that while the UN's actions broke the political deadlock, they were in violation of the principles outlined in of the United Nations Charter. The precedents illustrated the UN's inconsistent approach in contentious situations.